RELATIONSHIP OF KNOWLEDGE LEVEL ABOUT HYPERTENSION WITH DIETARY COMPLIANCE IN HYPERTENSION SUFFERERS RT 007 / RW 004 SUKARINGIN VILLAGE BEKASI IN 2022 - Veronica, Indah; Lina Indrawati; Ani Anggraeni (Rena Cipta Mandiri, 2024)
Hypertension is one of the most dangerous health problems around the world because hypertension is the main risk factor leading to cardiovascular disease. The emergence of health problems is not only caused by the ignorance of society as a result of the lack of correct information about a disease. This is because the low knowledge makes patients not know how to implement a hypertensive diet, where the lack of patients looking for information about the hypertensive diet affects health and a healthy lifestyle. This study aims to find out the relationship between knowledge levels and dietary compliance in the Sukaringin region, Bekasi regency. The research method used is quantitative with a cross sectional type of analytical research. The population of this study is the people in Sukaringin village. Based on the results of the study there is a relationship of knowledge level with adherence to hypertensive diet in Sukaringin village.